RANCANG BANGUN APLIKASI E-MODUL GUNA PEMANFAATAN PEMBELAJARAN DARING BERBASIS ANDROID - Azwar Azwar; La Diu Samiu (Jurnal Technopreneur (JTech), 2021)
The learning process that usually takes place face-to-face has changed to distance learning (Online Learning). This change is quite fast, so problems arise that not only occur in changes in the learning process but also in the readiness of learning media. Online Learning Requires a fairly high cost to provide internet package facilities to students. For this reason, it is necessary to change the form of learning media in this case the Module into the form of Digital Electronic Module (E-Modul). E-Module in the form of mobile android is a solution that can answer these problems. Applications in the form of Mobile have several advantages, such as being efficient in their use and not spending a lot of time or money because they can be used offline. For this reason, this study aims to design an E-Module Application for the Utilization of Android-Based Online Learning with the research method carried out using Research and Development (R&D) techniques. System testing is done using black box testing techniques and user accepted testing. Based on the results of the tests carried out, it is known that the responses from respondents to the questionnaires distributed are quite good with a percentage of 76%, while the results of user accepted testing (UAT) on design indicators are 82%, convenience is 83% and the efficiency of e-modules gets a presentation of 86 % so that the acceptance aspect of the system (E-Module) to the user is represented by 84% with a good scale.